Smart and Sustainable Operations Management in the Aviation Industry : A Supply Chain 4.0 Perspective - Paksoy, Turan; Demir, Sercan (Smart and sustainable operations and supply chain management, 2025)
"The ongoing impact of Industry 4.0 and disruptive technologies has transformed conventional supply chains into globally connected collaborative networks. As supply chains turn into flexible, agile, and digital structures, the planning and operation phases of the key business processes become more complex. This book presents state-of-art chapters on smart and sustainable supply chain management in the aviation industry. This book covers a wide range of topics, including key business operations in aviation, productivity improvement strategies in the aviation industry, and promising applications of disruptive technologies for aviation companies"--